The "Joyce Brain Atlas" Project: Mapping the Neuro-Architecture of Modernity - O' Connor, Theresa (Trinity College Dublin, 2007)
Like "Second Skin", a dynamic model of architecture pioneered by Marcos Lutyens at the Architectural Association in London, Finnegans Wake asks the reader to extend his/her consciousness to become a co-producer of an emergent architecture, in this case, a virtual city Joyce calls "Doublends Jined." Joyce's work does not provide answers. It offers an experimental playground in which a coming architecture and a coming model of identity as a multi-focal entity might be mapped out. The aim of the "Joyce Brain Atlas" Project is to uncover the "brain plan" of "Doublends" and build a brain navigator to guide us through its memory space, its landscape/mindscape.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: James Joyce; Neuro-architecture; Neuroscience; Architecture; Literature; Computer Science